2015
DOI: 10.1016/j.cpr.2015.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Burnout–depression overlap: A review

Abstract: Whether burnout is a form of depression or a distinct phenomenon is an object of controversy. The aim of the present article was to provide an up-to-date review of the literature dedicated to the question of burnout-depression overlap. A systematic literature search was carried out in PubMed, PsycINFO, and IngentaConnect. A total of 92 studies were identified as informing the issue of burnout-depression overlap. The current state of the art suggests that the distinction between burnout and depression is concep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
530
2
40

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 636 publications
(642 citation statements)
references
References 195 publications
(253 reference statements)
30
530
2
40
Order By: Relevance
“…Burnout can be characterized by a ‘core dimension’ that includes physical and mental exhaustion [4,5]. In addition, burnout may be associated with a sense of emotional distance to the curriculum or to patients in the sense of increased ‘cynicism’ [6–8].…”
Section: Introductionmentioning
confidence: 99%
“…Burnout can be characterized by a ‘core dimension’ that includes physical and mental exhaustion [4,5]. In addition, burnout may be associated with a sense of emotional distance to the curriculum or to patients in the sense of increased ‘cynicism’ [6–8].…”
Section: Introductionmentioning
confidence: 99%
“…Various studies have examined the relationship between burnout and depression and have yielded mixed results on whether burnout should be viewed as a distinct phenomenon or as a symptom of depression (Bianchi et al, 2015; Thuysma & De Beer, 2016). Burnout has been reported to predict depressive symptoms, and Thuynsma and De Beer (2016) found that depressive symptoms (together with job demands and satisfaction with life) explained significant amounts of variance in the burnout construct.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between burnout and depression is frequently explored in the literature (Bianchi, Schonfeld, & Laurent, 2015); burnout has been reported to predict depressive symptoms (Ahola, 2007) and life dissatisfaction. Thuynsma and De Beer (2016) also found depressive symptoms and satisfaction with life (together with job demands) to explain significant amounts of variance in the burnout construct.…”
Section: Introductionmentioning
confidence: 99%
“…Burnout is conceptualized as a multidimensional stress syndrome that comprises reduction of physical and emotional energies (2). The concept of burnout is not without drawbacks, however, as there is some significant overlap with depressive disorders (1,10,11) and an association with anxiety concepts (12,13). Therefore the diagnosis "burnout" is not included in DSM V and ICD-11 due to some lack of clarification.…”
mentioning
confidence: 99%